Atypical Wilson disease-A case report with CT scan - Misra Madhumati; Mohanty Amar; Rath Sanathan (Indian Journal of Ophthalmology, 1989)
A case of atypical Wilson disease is being reported. Possible mechanism of the process, diagnostic features and CT appearance of brain is described. Early detection and therapy with copper chelating agents result in neurologic and performance improvement of patients.